The relationship between emotional intelligence, sensation seeking and marital satisfaction among female teachers - Hatam Siavoshi; Ali Jahanian; Mojtaba Abbasi Asl; Mohammad Mafakheri (Shahid Beheshti University of Medical Sciences, 2016)
Background and objective: The purpose of this research is to study the relation between emotional intelligence, sensation seeking and marital satisfaction among female teachers in the city of Borujerd. Materials and Methods: The statistical population is consisted of all married female teachers in the city of Borujerd, 100 of whom were selected as the sample by random cluster sampling method. To collect the data Enrich marital satisfaction questionnaire, Bar-On emotional intelligence questionnaire, and Zuckerman sensation seeking questionnaire were used. Data analysis was done using SPSS software, Pierson's correlation test and stepwise regression. Results: The results of the analysis indicated that with significance level of p≤0.01 there is a negative and significant relation between sensation seeking and marital satisfaction; and with significance level of p≤0.01 there is a positive and significant relation between emotional intelligence and marital satisfaction. Also with significance level of p≤0.05 there is a significant relation between sensation seeking and emotional intelligence. Conclusion: Considering the findings of the present study, sensation seeking and emotional intelligence have a significant relation with marital satisfaction. Increase in emotional intelligence is accompanied with decrease in sensation seeking which consequently leads to marital satisfaction. Keywords: emotional intelligence, sensation seeking, marital satisfaction, female teachers.